Establishment of an internationally based offshore branch campus: an Australian case study - Wood, Raynie L., author; Strathe, Marlene, advisor; Anderson, Sharon, committee member; Weinberger, Andrea, committee member; Elliot, Jonathan, committee member; Zahavich, Alex, committee member (Colorado State University. Libraries, 2017)
As a result of the changes in society due to globalization, higher-education organizations are working to prepare graduates for a more global workplace. One of the methods of transnational education recognized for providing access to a global education is the international branch campus (IBC). While there are various types of international partnerships, the IBC is acknowledged for having benefits, and administrators acknowledge that there are significant risks. This qualitative methods case study explored an Australian source campus that engaged in the establishment of a Middle Eastern host campus. The central research questions were 1) what were the decision-makers' perceptions of the decision-making process when considering the establishment of an IBC, and 2) what were the indicators used to measure the success of the IBC. The findings of this case were that, while many stakeholders contributed to the decision-making process, the CEO was identified as the final decision-maker. The decision-making process was not linear in nature, consisting of various go/no-go decision points. While this organization had a history of engagement in IBCs, it was felt that due to the nature of this partnership there was increased risk requiring a range in due diligence assessments. The measures of success were clearly aligned with financial and quality indicators. While the host operations were viewed as being very different, the source operation's standard annual reporting benchmarks and goals, and timelines to monitor success were used.